Prosthodontic procedural treatment consideration in pandemic situation: a review - Juanita, Mariska; Jubhari, Eri Hendra; Utama, Mohammad Dharma (Indonesia Prosthodontic Association, 2021)
The global spread of the coronavirus disease has put dentists, dental specialists, and staff, as well as patients, at danger of COVID-19 infection during dental procedures. The COVID-19 risk associated with prosthodontic dental treatment operations might range from low to very high. This article provides a helpful guide to prosthodontic treatment processes, including infection control and standards of care.